In vitro Antiproliferative and Apoptosis Inducing Effect of Allium atroviolaceum Bulb Extract on Breast, Cervical, and Liver Cancer Cells - Khazaei, Somayeh; Esa, Norhaizan M.; Ramachandran, Vasudevan; Hamid, Roslida A.; Pandurangan, Ashok K.; Etemad, Ali; Ismail, Patimah (Frontiers in Pharmacology, 2017)
Abstract Natural products are considered potent sources for novel drug discovery and development. The multiple therapeutic effects of natural compounds in traditional medicine motivate us to evaluate the cytotoxic activity of bulb of Allium atroviolaceum in MCF7 and MDA-MB-231, HeLa and HepG2 cell lines. The bulb methanol extract of Allium atroviolaceum was found to be an active cell proliferation inhibitor at the time and dose dependent manner. Determination of DNA content by flow cytometry demonstrated S and G2/M phase arrest of MCF-7 cell, correlated to Cdk1 downregulation, S phase arrest in MDA-MB-231 which is p53 and Cdk1-dependent, sub-G0 cell cycle arrest in HeLa aligned with Cdk1 downregulation, G0/G1, S, G2/M phase arrest in HepG2 which is p53-dependent. Apoptosis as the mechanism of cell death was confirmed by morphology study, caspases activity assay, as well as apoptosis related gene expression, Bcl-2. Caspase-8, -9 and -3 activity with downregulation of Bcl-2 illustrated occurrence of both intrinsic and extrinsic pathways in MCF7, while caspase-3 and -8 activity revealed extrinsic pathway of apoptosis, although Bcl-2 downregulated. In HeLa cells, the activity of caspase-9 and -3 and downregulation of Bcl-2 shows intrinsic pathway or mitochondrial pathway, whereas HepG2 shows caspase independent apoptosis. Further, the combination of the extract with tamoxifen against MCF7 and MDA-MB-231 and combination with doxorubicin against HeLa and HeG2 demonstrated synergistic effect in most concentrations, suggests that the bulb of Allium atroviolaceum may be useful for the treatment of cancer lonely or in combination with other drugs.